Photovoltaic activity in a ZnSe/PEO-chitosan blend electrolyte junction - Mohamad, S.A.; Ali, M.H.; Yahya, R.; Ibrahim, Z.A.; Arof, Abdul Kariem (Springer Verlag (Germany), 2007)
Thin films of ZnSe and PEO-chitosan blend polymer doped with NH 4I and iodine crystals were prepared to form the two sides of a semiconductor electrolyte junction. ZnSe was electrodeposited on indium tin oxide (ITO) conducting glass. The polymer is a blend of 50 wt chitosan and 50 wt polyethylene oxide. The polymer blend was complexed with ammonium iodide (NH 4I), and some iodine crystals were added to the polymer-NH 4I solution to provide the I -/I 3-redox couple. The room temperature ionic conductivity of the polymer electrolyte is 4.32âÃâ10 -6 S/cm. The polymer film was sandwiched between the ZnSe semiconductor and an ITO glass to form a ZnSe/polymer electrolyte/ITO photovoltaic cell. The open circuit voltage (V oc) of the fabricated cells ranges between 200 to 400 mV and the short circuit current between 7 to 10 Î¼A.